Multiparameter Collaborative Optimization and Analysis of the Non-Penetrating Tunnel Thruster - Jinyu Guo; Yi Yang; Chao Wang; Zhiqiang Hu; Quan Zheng; Chuanzhi Fan (Journal of Marine Science and Engineering)
A brand new non-penetrating tunnel thruster (short for NPT thruster) is proposed in this paper. The tunnel structural parameters of the thruster are optimized, and the performance and optimization effect are verified by experiments. First, the design and function of the NPT thruster are introduced. Second, the computational fluid dynamics method is used to calculate the hydrodynamic performance of the NPT thruster and to analyze the static mooring thrust performance. Third, the tunnel structural parameters of the NPT thruster are optimized with the method of the response surface methodology. The pressure distributions and the flow fields on the tunnel surface of the NPT thrusters before and after optimization are compared with simulations. Finally, the mooring static thrust of the NPT thrusters is tested with experiments. The results show that the average increase in the mooring static thrust for the optimized thruster is 12.4%, and the maximum increase can reach 21.79% when the rotational speed is from 3000 rpm to 6500 rpm.